'I Don't Want to See that the People Are Suffering': Nurses in an Impoverished Community Talk About Caring for Women Following Stillbirths. (7th May 2020) - Lappeman, Maura; Swartz, Leslie
Abstract : This article explores the way in which nurses working in a high‐risk and dangerous environment understand and speak about their work caring for mothers following stillbirths. As far as we are aware, it is the first study of its kind from a low‐ or middle‐income country, and the first on this topic to apply the theoretical insights of Menzies Lyth in such contexts. In order to obtain rich exploratory data, a qualitative research methodology was used. The primary data source was interviews with nurses about their practices with women who have stillbirths. Reflecting on the findings from these interviews, we believe that the nurses' disclosures followed an overarching narrative that connected their cultural identity and personal suffering to the care that they administer. These connections between identity and profession perpetuate a healthcare system where the nurse often gives, not only out of duty and selflessness, but also out of her own sense of vulnerability. As hospitals in low‐income countries seek to improve their capacity to heal and support those in need of medical attention, nurses should be a focus of research. While their role is generally seen as a support to the doctors, in the case of stillbirths, they are far more central and often ill‐equipped for their role as grieving partner. Nurses need to be acknowledged and adequately supported.